Participatory alignment: a positive relationship between educators and students during online masters dissertation supervision. Issue 6 (18th August 2022) - Aitken, Gillian; Smith, Kelly; Fawns, Tim; Jones, Derek
ABSTRACT: The expansionist nature of the higher education sector has led to an increase in the provision of online Masters programmes. Many of these programmes are offered part-time attracting working professionals. The dissertation component that can be the culmination of many of these degrees is largely unexplored. A constructivist grounded theory investigation of the relationship between online Masters dissertation students and their supervisors was undertaken. Five supervisors identified a recent graduate and each were interviewed independently; interviews were undertaken online and audio-recorded. Transcripts were analysed and resultant themes considered in terms of establishing, and then maintaining, the relationship. A model of participatory alignment is proposed to describe the relationship that developed online in this group of supervisors and graduates, based on aligned expectations and behaviours, building on the idea of supervision as a partnership. We propose there is a zone of participatory alignment with both under and over-alignment becoming potentially problematic.